2020
DOI: 10.1007/s10753-020-01298-7
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Regulation of miR-126 on Inflammation,Th17/Treg Subpopulation Differentiation, and Lymphocyte Apoptosis through Caspase Signaling Pathway in Sepsis

Abstract: To observe the inflammatory response, differentiation of Th17/Treg subsets and apoptosis of lymphocytes, by regulating miR-126 in lymphocytes of septic rats. After using cecal ligation and puncture to establish sepsis model, miR-126 mimic and miR-126 inhibitor were used to transfect lymphocytes of septic rats in vitro and in vivo. ELISA was used to detect TNF-α, IL-6, IL-17, and IL-10, the differentiation of Th17 and Treg was measured by flow cytometry, and apoptosis of lymphocytes was observed by fluorescence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
3
15
0
Order By: Relevance
“…After transfection of miR-126 mimics and inhibitors, we found that the expression of miR-126 was changed in T lymphocytes (Fig. 3 a), and the differentiation was changed of Th17/Treg, which was consistent with our previous study, Induction of Th17/Treg differentiation through apoptosis pathway can change the inflammatory factors in septic rats [ 20 ]. We analyzed the Th17 and Treg in peripheral blood of septic rats after miR-126 intervention.…”
Section: Resultssupporting
confidence: 90%
“…After transfection of miR-126 mimics and inhibitors, we found that the expression of miR-126 was changed in T lymphocytes (Fig. 3 a), and the differentiation was changed of Th17/Treg, which was consistent with our previous study, Induction of Th17/Treg differentiation through apoptosis pathway can change the inflammatory factors in septic rats [ 20 ]. We analyzed the Th17 and Treg in peripheral blood of septic rats after miR-126 intervention.…”
Section: Resultssupporting
confidence: 90%
“…Anti-CD28 reduced CLP-induced splenocytes apoptosis T lymphocyte subsets differentiation and lymphocytes apoptosis played an important role in septic rats [26,27]. The proportion of spleen cell apoptosis was signi cantly increased in CLP mice, with reduced nucleus number, irregular shape of the nucleus, state of condensation or nuclear fragments appear, while anti-CD28 relieved such spleen apoptosis signi cantly (Fig.…”
Section: Patient Characteristics and Comparisonmentioning
confidence: 88%
“…Interestingly, miR-126, miR-132, miR-221, and miR-625-3p were also connected with the antibody titers or serum-cytokine levels after vaccination in our regression analyses. miR-126 inhibits VCAM-1 expression in endothelial cells, thereby reducing leukocyte adherence to endothelial cells 29 , and miR-126 is known to be increased in sepsis 39 . miR-126-5p, which is produced from the same pre-miR-126 RNA as miR-126 is, binds to capsase-3 and prevents dimerization of the caspase 40 .…”
Section: Discussionmentioning
confidence: 99%